Exploring resident perspectives and practical approaches to water quality maintenance in communal boarding facilities: Implications for public health and hygiene - Wibowo, Jessica Mackenzie; Widodo, Jovanka Kanaya; Husain, Rena Anggraena; Kinder, Kayla Okta; Anthonius, Ferdy; Kurniawan, Markus (Applied Environmental Science, 2025)
Background: Water is a fundamental human resource, and ensuring its safety is essential for public health, especially in residential settings such as boarding houses. Water contamination can pose significant risks to residents’ well-being. This study focuses on exploring the water quality at a boarding house located on Bangka Street, South Jakarta, considering the importance of water clarity, taste, odor, and the infrastructure that supports water distribution. Methods: This research uses a descriptive qualitative approach, using semi-structured interviews and field observations. Data were collected directly from the boarding house owner and several residents to understand their perspectives and experiences regarding water usage and quality. Observations focused on water clarity, smell, taste, and the physical condition of the water infrastructure. Findings: The results show that the boarding house's water quality is generally clean, clear, and odorless—meeting national standards for safe water. However, an incident was reported in which excessive water use by a resident led to flooding and temporarily murky water. In response, the owner promptly drained the water tank and replaced outdated water pumps to restore water quality. These actions demonstrate the owner’s proactive maintenance and strong hygiene awareness. Conclusion: This study emphasizes the importance of regular water system monitoring, immediate responsiveness to water-related issues, and the collaboration between property managers and residents in maintaining water quality. Subjective perspectives reveal that a sense of shared responsibility and consistent maintenance are vital in ensuring access to clean and safe water in communal residential settings. Novelty/Originality of this article: This research contributes original insights into water quality management in small-scale residential environments. It highlights the value of community-level engagement and practical hygiene practices, combining lived experiences with public health standards to promote safe water access in boarding houses—a relatively underexplored area in academic literature.